2016
DOI: 10.1007/978-1-4939-3197-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Binding Studies Using MicroScale Thermophoresis

Abstract: The characterization and development of highly specific aptamers requires the analysis of the interaction strength between aptamer and target. MicroScale Thermophoresis (MST) is a rapid and precise method to quantify biomolecular interactions in solution at microliter scale. The basis of this technology is a physical effect referred to as thermophoresis, which describes the directed movement of molecules through temperature gradients. The thermophoretic properties of a molecule depend on its size, charge, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…The Soret coefficient ST: chot/ccold = exp(-ST ΔT) provides a quantitative measure for this effect and is depending on the size, charge and hydration shell of the molecules. Upon molecular interaction, at least one of these parameters is changed, resulting in distinct thermophoretic movements of the unbound and bound states [31]. …”
Section: Resultsmentioning
confidence: 99%
“…The Soret coefficient ST: chot/ccold = exp(-ST ΔT) provides a quantitative measure for this effect and is depending on the size, charge and hydration shell of the molecules. Upon molecular interaction, at least one of these parameters is changed, resulting in distinct thermophoretic movements of the unbound and bound states [31]. …”
Section: Resultsmentioning
confidence: 99%
“…While highly sensitive techniques employing radioactivity and SPR can measure K d up to sub-picomolar range; Fluorescence and ITC can measure K d limited to nanomolar and spectrophotometry techniques can measure K d in micromolar range. Recently, MicroScale Thermophoresis (MST), a novel low cost highly sensitive technique has been described by numerous aptamer—research groups that can estimate apparent dissociation constant in pico to nanomolar range, with high accuracy in limited microliter scale solutions (Stoltenburg et al, 2015 ; Breitsprecher et al, 2016 ; Entzian and Schubert, 2016 ; Jauset Rubio et al, 2016 ). In addition to less volume and unlike several techniques, MST also offers the advantage, that it can estimate the aptamer K d independent of the target size in wide range of buffers as well as in complex biological samples, in pico to nanomolar range (Entzian and Schubert, 2016 ).…”
Section: Enhancing Aptamer Evaluation Parametersmentioning
confidence: 99%
“…Therefore, the thermophoresis changes as a function of ligand concentration allow calculating dissociation constants ( K d ) [40]. Several MST applications for aptamer research have been reported (see [42] for detailed methods). Here, we label the aptamer with a fluorescent probe (probe FAM ) and use it at a constant concentration and increased the concentrations of HMG-box Pf , ranging from 0.1 nM to 2 μM.…”
Section: Resultsmentioning
confidence: 99%